Rediscovery and phylogenetic position of the glassfrog “Centrolene”acanthidiocephalum (Ruiz-Carranza and Lynch, 1989) (Anura: Centrolenidae)with the description of its advertisement call and comments on clutches and tadpoles - Carvajal-Cogollo, Juan E.; Quiroga-Huertas, Karol A.; Muñoz-Castro, Johana A.; Hernández-Avendaño, Paola; González-Durán, Gustavo A.; Meza-Joya, Fabio Leonardo (Zootaxa, 2023)
The lack of basic natural history and distributional data represents a challenge for the conservation of rare and endemic amphibian species. This is the case of “Centrolene” acanthidiocephalum, a poorly known glassfrog endemic to the Cordillera Oriental of the Colombian Andes. This species was formally described in the late 1980s and no records have been reported over the last quarter century. Therefore, little is known about its distributional boundaries, morphological variation, natural history, and evolutionary relationships. Here we report the finding of a population of “Centrolene” acanthidiocephalum from a locality around its historical range and provide additional information on its geographic distribution, clutch size, and adult morphology. We also present for the first time data on tadpole morphology, as well as a description of its advertisement call and a phylogenetic tree based on mitochondrial genetic data corroborating its generic position within Centrolene.